EFFECT OF MICROENCAPSULATED NAPROXEN INTO POLY(LACTIDE-COGLYCOLIDE)MICROSPHERES ON CARRAGEENIN PAW EDEMA IN RATS - ARAGÓN N., Diana M.; VERGEL B., Nadezdha E.; OSPINA G., Luis F.; MARTÍNEZ R., Fleming Departamento de Farmacia. Universidad Na; ROSAS P., Jaiver E. (Vitae, 2010)
Microparticles are pharmaceutical dosage forms widely used because they may improve the therapeutic application of new and conventional drugs. In this work we make biodegradable microparticles with poly (lactic-co-glicolic) acid as polymer loaded with naproxen. The best microencapsulation conditions are experimentally determinate. We have found that the drug:polymer ratio, the isopropanol amount, the aqueous phase volume, the stir speed and the time of stir affect the microparticles characteristics. In the carragenin paw edema model, we have found that the microencapsulated naproxen at 5 mg/Kg and 10 mg/Kg showed greater effect than free naproxen at 10 mg/Kg.